Konsep Pendidikan Islam Menurut Ibnu Sina dan Ibnu Qayyim Al Jauziyyah - Ansari Ansari; Ahmad Qomarudin (ISLAMIKA, 2021)
This study aims to describe the concept of Islamic education thought by Ibn Sina and Ibn Qayyim Al-Jauziyyah. The development of Islamic education thinking is important to improve and develop the quality of Islamic education in schools so that they can compete at the international level. The research method is descriptive qualitative and the data collection technique is a library study. The results of this study illustrate that there are fundamental differences from the concept of Islamic education thought both initiated by Ibn Sina and Ibn Qayyim, Ibn Sina's own thoughts are more inclined to the application of knowledge that is adapted to the age level of the child, while Ibn Qayyim's thinking is more inclined to inculcating values ​​of faith and the use of reason to develop children's thinking horizons. However, the thoughts of the two Muslim figures can still be used as a relevant reference in developing Islamic education in Muslim countries around the world, one of which is in Indonesia.